Biomonitoring of 2, 4, 6-trinitrotoluene and degradation products in the marine environment with transplanted blue mussels (M. edulis). (1st September 2017) - Strehse, Jennifer S.; Appel, Daniel; Geist, Catharina; Martin, Hans-Jörg; Maser, Edmund
Abstract: Since World War I considerable amounts of warfare material have been dumped at sea worldwide, but little is known about the fate of the explosive components in the marine environment. Sea dumped munitions are able to contaminate the surroundings because of the release of explosive chemicals due to corrosion and breaching or by detonation after blast-operations. This implies the risk of accumulation of toxic compounds in human and wildlife food chains. With the help of divers, we performed an active biomonitoring study with transplanted blue mussels ( M. edulis ) in a burdened area (Kolberger Heide, Germany) with explosive compounds near blast craters over an exposure time of 93 days. With this biomonitoring system, we could show that blue mussels accumulate 2, 4, 6-trinitrotoluene (TNT) and its metabolites 2-amino-4, 6-dinitrotoluene (2-ADNT) and 4-amino-2, 6-dinitrotoluene (4-ADNT) in their tissues. In all mussels deployed at the ground, we found a body burden with 2-ADNT of 103.75 ± 12.77 ng/g wet weight and with 4-ADNT of 131.31 ± 9.53 ng/g wet weight. TNT itself has been found in six mussels with an average concentration of 31.04 ± 3.26 ng/g mussel wet weight. In the mussels positioned at one meter above the ground no TNT nor 2-ADNT could be detected, but 4-ADNT was found in all samples with an average concentration of 8.71 ± 2.88 ng/g mussel wet weight. To the best of our knowledge, this is the first study using blue mussels M. edulis as an active biomonitoring system for TNT and its metabolites 2-ADNT and 4-ADNT in a free field experiment in a burdened area. Moreover, with this system, we unequivocally proved that these toxic explosives accumulate in the marine biota resp. in the marine food chain, thereby posing a possible risk to the marine ecosphere and human health.